2017
DOI: 10.1002/slct.201701354
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Protocol for Palladium N‐Heterocyclic Carbene‐Catalysed Suzuki‐Miyaura Reaction at room temperature

Abstract: International audienceThe palladium-N-heterocyclic carbene complexes have been synthesised from 1,3-bis-(N-alkyl) benzimidazolium salts and catalytic activity of complexes have been tested on Suzuki-Miyaura coupling reaction for aryl bromides with substituted arylboronic acids at room temperature in i-PrOH/water. Structural characterisation of palladium complex 2b was determined by x-ray crystallography. A convenient and effective protocol has been evolved that has several superior advantages, including very l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 86 publications
0
11
0
Order By: Relevance
“…In this manner, to increase the solubility of catalyst precursors in aqueous media, our strategy was based on the synthesis of ionic Pd(II)-NHC complexes (Scheme 1). With this aim, we chose symmetrical 1,3-bisalkylbenzimidazolium precursors (1a-1c), which were previously used in the synthesis of neutral Pd-NHC complexes [22][23][24]. These results may provide knowledge about the catalytic activities of neutral and ionic Pd-NHC complexes, which bear the same NHC ligands.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this manner, to increase the solubility of catalyst precursors in aqueous media, our strategy was based on the synthesis of ionic Pd(II)-NHC complexes (Scheme 1). With this aim, we chose symmetrical 1,3-bisalkylbenzimidazolium precursors (1a-1c), which were previously used in the synthesis of neutral Pd-NHC complexes [22][23][24]. These results may provide knowledge about the catalytic activities of neutral and ionic Pd-NHC complexes, which bear the same NHC ligands.…”
Section: Resultsmentioning
confidence: 99%
“…It is believed that these salts help to stabilize or maintain stable active species via the coordination or formation of ion pairs [18,21]. Thus, the synthesis and investigation of catalytic activity of ionic type Pd(II)-NHC complexes may be interesting and nice to compare with the catalytic activity of Pd(II)-NHC on Suzuki-Miyaura reactions [22][23][24]. Our earlier investigations showed that neutral PdX 2 (NHC) 2 , PdX 2 (NHC)pyridine Scheme 1.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous ONO, NNN, PCP, PNP and NCN pincer complexes have been reported, which act effectively as catalysts for the coupling reactions, C‐H activation, water splitting, asymmetric transformations, etc . Designing such pincer ligands has drawn enormous attention in the past few years .…”
Section: Introductionmentioning
confidence: 95%
“…Though many chemists have studied the effect of different pincer ligands on the catalytic activity of their complexes, only little attention has been paid to understand the role of ancillary ligand in pincer complexes. Our focus towards this direction has already achieved phosphine‐free Pd(II)‐NNN pincer catalysts for the SMC reaction, where we have found that CH 3 CN can replace PPh 3 ancillary ligand without compromising the activity . Subsequently we have compared the catalytic activity between the pincer complexes containing CH 3 CN ( sp hybridized N) ancillary ligand and those with bulky 2‐bromopyridine ( sp 2 hybridized N), towards the same SMC reaction; the results are being presented in this paper.…”
Section: Introductionmentioning
confidence: 99%
“…This synthesis approach has revolutionized the production of advanced materials [15,16,17,18], pharmaceuticals [19,20,21], agrochemicals [21,22], liquid crystals [23], and natural or biologically active compounds [24,25,26,27,28], etc. Numerous attractive strategies have been developed to address the ample scope of this catalytic process including the utilization of palladium nanoparticles [29,30,31,32,33,34,35], or palladium immobilized on magnetic nanoparticles [36] and natural supports [37], use of nucleophilic carbene ligands (mostly NHCs) [38,39,40,41,42,43,44,45,46], Schiff bases [47,48], water-soluble ligands like poly(ethylene glycol)-functionalized N-heterocyclic carbenes [49], thiourea [50] or phosphines [51,52], induction by microwave (MW) acceleration [53,54], use of “greener” solvents, such as water [55,56,57,58,59,60,61,62,63,64,65] (activated by MW [66,67] or in catalysis under micellar conditions [68] for enhancing the solubility of the aromatic halide), water–DMF […”
Section: Introductionmentioning
confidence: 99%